National census of availability of neonatal intensive care - Parmanum, Jill (BMJ, 2000)
OBJECTIVE: To determine whether availability of neonatal intensive care cots is a problem in any or all parts of the United Kingdom. DESIGN: Three month census from 1 April to 30 June 1999 comprising simple data sheets on transfers out of tertiary units. SETTING: The 37 largest high risk perinatal centres in the United Kingdom. PARTICIPANTS: One obstetric specialist and one neonatal specialist in each centre. MAIN OUTCOME MEASURES: Suboptimal care resulting directly from pressure on service—that is, transfers out of tertiary units (either in utero or after delivery) because the unit was “full” and not because the hospital was incapable of providing the care needed. RESULTS: All units provided data. The number of intensive care cots in each unit was between five and 16. During the three months 309 transfers occurred (equivalent to 1236 per year), of which 264 were in utero and 45 postnatal. Sixty five in utero transfers involved multiple births, hence the census related to 382 babies (1528 per year). There was considerable regional variation. The reason for transfer in most cases was “lack of neonatal beds”. CONCLUSIONS: Currently most major perinatal centres in the United Kingdom are regularly unable to meet in-house demand; this has implications for the service as a whole. The NHS has set no standards to help health authorities and primary care groups develop services relating to this specialty; such a step may well be an appropriate lever for change.